Analysis of Municipal Election Outcomes in Romania - Dorin Jula; Nicolae-Marius Jula (European Regional Science Association (ERSA), 2011)
In Romania, the 2008 local elections were held based on a new electoral law. The main changes concerned the election of chairpersons of county councils by uninominal voting, shifting of the general and presidential elections and the introduction of a uninominal voting system for parliamentary elections, with a correction of the total number of seats according to the total number of votes obtained by each party on national level. Voting behavior in local elections on 1st June 2008 was primarily determined by political reasons (loyal voters) and was influenced by the effect of the local leaders and the noise produced by ethnic vote. For all parties, prominent leaders drew votes. Inertia in voting behavior (electorate's fidelity) influenced all parties' results and the ethnic behavior had a strong effect on nationalist parties. At regional level, the electoral impact of economic variables was marginal.
Keywords: 330